2014
DOI: 10.1002/mrd.22333
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic target of rapamycin (MTOR) signaling during ovulation in mice

Abstract: A complex network of endocrine/paracrine signals regulates granulosa-cell function in ovarian follicles. Mechanistic target of rapamycin (MTOR) has recently emerged as a master intracellular integrator of extracellular signals and nutrient availability. The objectives of the present study were to characterize the expression pattern and kinase activity of MTOR during follicular and corpus luteum development, and to examine how inhibition of MTOR kinase activity affects preovulatory maturation of ovarian follicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Interestingly, though the expressions of eIF4B and S6 were higher in Dorset sheep than in Han sheep, the protein content of mitogen-activated protein kinase 1 (MAPK1), the upper stream regulator of mTOR pathway - also known as extracellular signal-regulated kinase 2 (ERK2), in Dorset group was significantly lower than in both Han groups. ERK1/2 plays an important role in animal ovulation, and the higher expression level of ERK1/2 in Han sheep may contribute to its higher ovulation rate compared with Dorset sheep32. Our proteomic results show that the roles of ribosome and mTOR pathway in the differences of sheep fecundity between Dorset and Han sheep need further study.…”
Section: Discussionmentioning
confidence: 76%
“…Interestingly, though the expressions of eIF4B and S6 were higher in Dorset sheep than in Han sheep, the protein content of mitogen-activated protein kinase 1 (MAPK1), the upper stream regulator of mTOR pathway - also known as extracellular signal-regulated kinase 2 (ERK2), in Dorset group was significantly lower than in both Han groups. ERK1/2 plays an important role in animal ovulation, and the higher expression level of ERK1/2 in Han sheep may contribute to its higher ovulation rate compared with Dorset sheep32. Our proteomic results show that the roles of ribosome and mTOR pathway in the differences of sheep fecundity between Dorset and Han sheep need further study.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, accumulating evidence suggests that the metabolic mTOR/PTEN/PI3K signaling pathways play crucial roles during follicular growth and oocyte development in mice [230, 231]. Genetic data have shown that all primordial follicles become depleted in early adulthood of mice lacking PTEN in oocytes, causing premature ovarian failure [232].…”
Section: Methodsmentioning
confidence: 99%
“…The mTOR pathway has been implicated in many cellular processes including protein translation and signalling from hormones, nutrients and growth factors (Huang & Manning, ; Kim, Goraksha‐Hicks, Li, Neufeld, & Guan, ). In this study, we observed that GnRH treatment increases mTOR activity in granulosa cells as revealed by the increase in p‐S6K (Siddappa et al., ) and RHEB (Guertin & Sabatini, ; Inoki, Li, Xu, & Guan, ) mRNA levels. This demonstrates that mTOR activity is inducted by gonadotropins in granulosa cells from preovulatory follicles of monovulatory species as previously observed in polyovulatory species (Siddappa et al., ; Yu et al., ).…”
Section: Discussionmentioning
confidence: 53%
“…This suggests the mTOR may participate in the regulation of EREG expression after LH surge. However, a previous study in mice observed that rapamycin injection could not prevent the upregulation of EREG mRNA induced by hCG treatment (Siddappa et al., ). This suggests that mTOR effect on EREG regulation may differ in monovulatory and polyovulatory species.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation